Parish and Belonging : Community, Identity and Welfare in England and Wales, 1700–1950 - Snell, K. D. M (Cambridge University Press, 2013)
‘Where do you come from?’ must be one of the most frequent opening conversational lines in English. It can be interpreted in a number of ways, yet it always produces a reply and reciprocal interest, and its answer often appears to be confirmed by accent, personality, and appearance. It may establish rapport, but occasionally arouses distrust